The Role of Ammonia in the Distribution of Volatiles in the Primordial Hydrosphere of Europa - Alizée Amsler Moulanier; Olivier Mousis; Alexis Bouquet; Christopher R. Glein (The Planetary Science Journal)
The presence of a hydrosphere on Europa raises questions about its habitability, and studies of its volatile inventory can provide insight into its formation process. Different scenarios suggest that Europa's volatiles could be derived from cometary ices or devolatilized building blocks. The study of post-accretion processes—in particular, the “open-ocean” phase that likely occurred before the formation of the icy crust—is crucial to distinguishing these origins, as this phase is likely to have influenced the volatile inventory. The abundance of ammonia in Europa's building blocks is also crucial for understanding the composition of its ocean and primordial atmosphere. We aim to investigate the ocean–atmosphere equilibrium during the post-accretion period by varying the ammonia fraction in the atmosphere. Our model evaluates the vapor–liquid equilibrium of water and volatiles, as well as the chemical equilibrium within the ocean, to study Europa's early hydrosphere. We explore two initial conditions: one in which Europa's hydrosphere originates from comet-like building blocks, and another in which it forms in equilibrium with a thick-and-CO _2 -rich atmosphere. In both scenarios, the initial ratio of accreted CO _2 to NH _3 determines the magnitude of their partial pressures in Europa's early atmosphere. If this ratio exceeds a certain threshold (set to 10 ^−4 in this study), the atmosphere will be CO _2 -rich; otherwise, it will be CO _2 -depleted, by multiple orders of magnitude. Overall, our work provides an initial assessment of the distribution of primordial volatiles in Europa's primitive hydrosphere and provides a baseline for interpreting data from the upcoming Europa Clipper mission.